Pengaruh Guerrilla Marketing dan Creativity terhadap Marketing Performance dengan Brand Awareness sebagai Variabel Mediasi pada Konsumen Somethinc di Kota Semarang - Fera Aprilliya; Ibnu Khajar (ARZUSIN, 2025)
Intensifying competition in the skincare industry between local and global brands requires companies to implement innovative and creative marketing strategies to improve marketing performance. The decline in Somethinc’s brand position in e-commerce sales rankings indicates the need to evaluate and strengthen its existing marketing strategies. This study aimed to analyze the effect of guerrilla marketing and creativity on marketing performance with brand awareness as a mediating variable among Somethinc consumers in Semarang City. The research employed a quantitative approach with an explanatory research design, involving 100 respondents selected through purposive sampling. Data were collected using a questionnaire and analyzed using multiple linear regression and the Sobel test with the assistance of SPSS. The findings show that guerrilla marketing and creativity have a positive and significant effect on brand awareness, and that brand awareness has a positive and significant effect on marketing performance. In addition, guerrilla marketing and creativity also have a direct positive effect on marketing performance, while brand awareness is proven to mediate the influence of both variables on marketing performance. The study concludes that non-conventional and creative marketing strategies, when supported by strengthened brand awareness, can significantly enhance marketing performance. In practical terms, local skincare companies are advised to optimize guerrilla marketing strategies and marketing creativity to reinforce brand awareness and competitiveness in the digital marketplace.